TES KOGNITIF DIAGNOSTIK UNTUK MENDETEKSI KESULITAN BELAJAR SISWA SEKOLAH DASAR - Sri Budyartati (Universitas PGRI Madiun, 2011)
Misconception refers to a concept which is neither in accordance with a scientific nor accepted by experts of a scientific body. Concepts are brought by students through observations or their first hand experiences of daily life. Students’ continuous misconceptions may hinder their building of scientific conceptions. Learning which does not take into account misconceptions leads learning difficulties and ends in students’ low achievement. In constructivistic learning, what does matter is that the learners themselves build their knowledge, rather than that the teacher transfers the knowledge. An implication of the constructivistic view for schools is that knowledge cannot be simply transformed from the teacher’s mind to the students’. It is actively constructed by the students themselves through first hand experiences. Teachers’ role, therefore, changes from the source and the giver of knowledge into the facilitator, and, by so doing, the essence of education lies on the learners rather than on the teacher. Cognitive Diagnostic Assessment (CDA) for education is designed specifically to assess the knowledge structure and the process of students’ ability to supply information with regard to their cognitive strength and weakness